2023
DOI: 10.1002/jee.20512
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofCOVID‐19 on sense of belonging: Experiences of engineering students, faculty, and staff at Historically Black Colleges and Universities (HBCUs)

Abstract: Background: COVID-19 has spurred a global crisis that has disrupted everyday lives and impacted the traditional methods, experiences, and abilities of higher education institutions' students, faculty, and staff, especially at Historically Black Colleges and Universities (HBCUs).Purpose/Hypothesis: Given the pressing need demonstrated by the National Academies to advance the utilization of science, technology, engineering, and mathematics (STEM) education at HBCUs, this study aimed to explore the abrupt transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Such a theoretical framework is fundamentally different from common framings such as diffusion of innovations (Rogers, 2003) or fidelity of implementation (Borrego et al, 2013;O'Donnell, 2008) in that an ecosystems perspective foregrounds and legitimizes local needs and values in negotiating uptake, potentially in ways inconceivable to those in more privileged contexts. Importantly, instructors need to nimbly respond to unanticipated perturbations to their instructional ecosystems, such as the disruptions from the COVID pandemic during this study (Fletcher et al, 2023;London et al, 2022) or the introduction of generative artificial intelligence tools like the ChatGPT chatbot that have recently emerged (Kasneci et al, 2023;Rudolph et al, 2023). A dynamic, ecosystems model fundamentally addresses instructor decision making around educational technology and pedagogical practices amidst these perturbations in ways that theories like fidelity of implementation are unable to.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a theoretical framework is fundamentally different from common framings such as diffusion of innovations (Rogers, 2003) or fidelity of implementation (Borrego et al, 2013;O'Donnell, 2008) in that an ecosystems perspective foregrounds and legitimizes local needs and values in negotiating uptake, potentially in ways inconceivable to those in more privileged contexts. Importantly, instructors need to nimbly respond to unanticipated perturbations to their instructional ecosystems, such as the disruptions from the COVID pandemic during this study (Fletcher et al, 2023;London et al, 2022) or the introduction of generative artificial intelligence tools like the ChatGPT chatbot that have recently emerged (Kasneci et al, 2023;Rudolph et al, 2023). A dynamic, ecosystems model fundamentally addresses instructor decision making around educational technology and pedagogical practices amidst these perturbations in ways that theories like fidelity of implementation are unable to.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional context played a role in the ways that instructors and students responded to the pandemic as well. For example, Fletcher et al (2023) attributed the positive culture of institutional support and sense of belonging at Historically Black Colleges and Universities (HBCUs) to their ability to navigate the shift to online instruction and to safely reopen campuses with fewer infection cases than non-HBCUs.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…Al Miskry, Hamid, and Darweesh (2021) conducted a study in the United Arab Emirates with students, faculty, and staff, and found that all participants' mental health and physical health were negatively impacted by the pandemic. Lastly, a study similar to ours is one that was conducted by Fletcher, Jefferson, Boyd, Park, and Crumpton-Young (2023) in engineering programs at Historically Black Colleges and Universities (HBCUs) in the US. They reported that faculty experienced more challenges with instruction, research, and mentorship during the pandemic.…”
Section: Key Global and Us-based Covid-19 Developments And Impacts On...mentioning
confidence: 99%
“…However, Black and African Americans continue to be disproportionately underrepresented among students attaining an engineering degree [10]. Within this population, Black women are twice as likely to enroll in higher education compared to Black men [11]. Yet, when it comes to engineering degree attainment over the past ten years, an average of only 24% of the Black recipients were women [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Within this population, Black women are twice as likely to enroll in higher education compared to Black men [11]. Yet, when it comes to engineering degree attainment over the past ten years, an average of only 24% of the Black recipients were women [10,11]. A well-documented solution to increasing Black girls' interest in engineering and more broadly, in STEM, has been exposure to the curriculum and programming through pre-college and informal activities and initiatives, especially those within informal settings [12][13][14].…”
Section: Introductionmentioning
confidence: 99%